Exploring caregiver influence on child creativity and innovation in an out-of-school engineering program. (September 2022) - Knox, Peter; Simpson, Amber; Yang, Jing; Maltese, Adam
Highlights: Creative and novel thinking is required to meet evolving STEM discipline needs. Creativity is often neglected or misperceived within typical classroom environments. Caregiver engagement impacts child learning, particularly in out-of-school contexts. Caregivers use several dialogic methods that influence child creativity and thinking. Child ideas and creative thinking around engineering stages are shaped by caregivers. Abstract: Creativity is of increasing importance to the field of engineering. Thus, furthering our understanding of the development of (or barriers to) creativity during childhood and adolescence, and in environments alternative to traditional classroom settings, may hold particular significance and implications for generating creative and cognitive shifts amongst children, and their ultimate interest in the discipline. Constraints on child creative thinking and innovation that may occur by educators and within schools highlight the need to explore alternative environments and individuals, such as caregivers and/or out-of-school contexts. To expand our understanding of the influence caregivers may have on child creativity and innovation, particularly during the critical engineering design phases of problem identification and solution ideation, this study sought to investigate how caregiver involvement shapes the creativity and innovation of children in an out-of-school engineering program. Using conversation analysis to examine caregiver-child dialogue, results demonstrate ways that child ideas, creative thinking, and innovative engagement with various solutions were shaped by caregivers' involvement through four predominant dialogic methods, including (a) directive questioning, (b) restating/reframing, (c) idea blending, and (d) using shared experiences. Insights into specific dialogic methods caregivers employed while engaging with children in out-of-school environments through the engineering design cycle are discussed, further illuminating how such engagement and specific conversational tactics impact children's creative thinking and use of innovation. In so doing, we support the argument that the nature of caregiver engagement and the fostering or hindering of creativity and innovation through conversation ultimately influences children's own engagement and application of engineering concepts